Abnormal Output Characteristics of p-Type Low Temperature Polycrystalline Silicon Thin Film Transistor Fabricated on Polyimide Substrate - Seok-Woo Lee; Chang Bum Park; Pyo Jin Jeon; Sung-Wook Min; June Yeong Lim; Han Sol Lee; Jae-Sung Yoo; Soon Sung Yoo; Seongil Im (IEEE Journal of the Electron Devices Society, 2016)
We report on an abnormal output characteristics in p-type low temperature polycrystalline silicon thin-film transistors fabricated on polyimide (PI); negative differential conductance behavior is often observed in saturation region of drain current from large width devices. To understand such abnormal output characteristics, device dimension dependence was studied in a systematic way. As a result, we found that enhanced self-heating is mainly responsible originating from the poor thermal conductivity of PI substrate. A related degradation model is also proposed.